2004
DOI: 10.2307/4135609
|View full text |Cite
|
Sign up to set email alerts
|

A review of research on the cycad genus Ceratozamia Brongn. (Zamiaceae) in Mexico

Abstract: The genus Ceratozamia contains more than 20 species distributed in eastern and southern Mexico, with extensions into Central America. Morphology, anatomy, and molecular (ITS) data allow resolution of some aspects of species relationships, provide correlations with ecology, and suggest phytogeographic hypotheses. Some species complexes, such as those centered around C. norstogii and C. miqueliana, are restricted to southernwest Mexico, in what are regarded as Pleistocene floristic refugia. The low level of dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…Few attempts have been made to review portions of the cycad literature (Vovides et al 2003(Vovides et al , 2004(Vovides et al , 2007Terry et al 2012). The immense literature on phylogeny and systematics is in effect reviewed with each update of "The World List of Cycads" that appears in each set of conference proceedings, but a review on how tools and methods have evolved over the years may be warranted.…”
Section: Suggestionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few attempts have been made to review portions of the cycad literature (Vovides et al 2003(Vovides et al , 2004(Vovides et al , 2007Terry et al 2012). The immense literature on phylogeny and systematics is in effect reviewed with each update of "The World List of Cycads" that appears in each set of conference proceedings, but a review on how tools and methods have evolved over the years may be warranted.…”
Section: Suggestionsmentioning
confidence: 99%
“…Cycads can be traced to the late Carboniferous period and offer unique research opportunities for contemporary scientists (Brenner et al 2003;Donaldson 2003). Nevertheless, the quantity and breadth of accessible published research on this ancient and important group of plants is limited (Dehgan 1983;Sabato & de Luca 1985;Moretti et al 1993;Norstog & Nicholls 1997;Vovides et al 2003Vovides et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus is endemic to Mega-Mexico ( sensu Rzedowski 1991), ranging from Mexico to Honduras. Mexico is considered the centre of diversity for Ceratozamia , given that 30 out of 31 recognised species occur in its territory (Vovides et al 2004a; Nicolalde-Morejón et al 2014), 90 percent of which are endemic (Calonje et al 2013-2018). Diversity for this genus is particularly prevalent along the Sierra Madre Oriental and Southwest Mexico, especially in the political states of Veracruz, Oaxaca, Chiapas and Tabasco.…”
Section: Introductionmentioning
confidence: 99%
“…In recent taxonomic works, quantitative morphological characters such as plant size and leaflet width have been commonly used as a basis for the identification and description of new species because they exhibit variability across the genus (Vovides et al 2004a, c; Whitelock 2004). However, other contemporary studies have shown that these characters can be highly variable between and amongst populations, which limits species diagnosis (Martínez-Domínguez et al 2016; 2017a, b, c).…”
Section: Introductionmentioning
confidence: 99%